The Role of The Government And Sharia Banks on MSME Communities And Coffee Farmers in Increasing Production Results to Fulfill The Export Needs of Arabica Coffee on Central Aceh District - Ikhsan fajri; Zuliani Zuliani (International Conference on Multidisciplinary Research, 2022)
The role of the government and Islamic financial institutions, both Bank Aceh and Bank Syariah Indonesia BSI, is certainly highly expected by MSME actors and coffee farmers in Central Aceh in responding to limited financial access which has been the dominant factor affecting the level of production quality and price stability of Arabica coffee complained by farmer. This study aims to determine the role of the Government and Islamic Financial Institutions towards MSMEs and Farmers in improving the quality of production and fulfillment of Arabica Gayo coffee exporters in Central Aceh Regency. This research method uses a qualitative design with case study research technique. Types of data collected are in the form of primary and secondary data. The results of this study are very useful and can be an insight for the government and financial institutions, both banks and non-banks, to continue to focus on providing sufficient access to the capital for farmers, MSME, and cooperatives in order to boost the quality of Arabica Gayo coffee production which is superior as one of Indonesia's philanthropic products for world. Keywords: The role of government , banks , export quality , Arabica coffee